A pilot study: dose adaptation of capecitabine using mobile phone toxicity monitoring - supporting patients in their homes. - Weaver, A; Love, S; Larsen, M; Shanyinde, M; Waters, R; Grainger, L; Shearwood, V; Brooks, C; Gibson, O; Young, A; Tarassenko, L (2014)
PURPOSE: Real-time symptom monitoring using a mobile phone is potentially advantageous for patients receiving oral chemotherapy. We therefore conducted a pilot study of patient dose adaptation using mobile phone monitoring of specific symptoms to investigate relative dose intensity of capecitabine, level of toxicity and perceived supportive care. METHODS: Patients with breast or colorectal cancer receiving capecitabine completed a symptom, temperature and dose diary twice a day using a mobile phone application. This information was encrypted and automatically transmitted in real time to a secure server, with moderate levels of toxicity automatically prompting self-care symptom management messages on the screen of the patient's mobile phone or in severe cases, a call from a specialist nurse to advise on care according to an agreed protocol. RESULTS: Patients (n = 26) completed the mobile phone diary on 92.6 % of occasions. Twelve patients had a maximum toxicity grade of 3 (46.2 %). The average dose intensity for all patients as a percentage of standard dose was 90 %. In eight patients, the dose of capecitabine was reduced, and in eight patients, the dose of capecitabine was increased. Patients and healthcare professionals involved felt reassured by the novel monitoring system, in particular, during out of hours. CONCLUSION: It is possible to optimise the individual dose of oral chemotherapy safely including dose increase and to manage chemotherapy side effects effectively using real-time mobile phone monitoring of toxicity parameters entered by the patient.